1986
DOI: 10.2307/3586387
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Language Learning as a Predictor of Success in Acquiring English as a Second Language

Abstract: This article reports the results of a study of the effectiveness of computer‐assisted language learning (CALL) in the acquisition of English as a second language by Arabic‐ and Spanish‐speaking students in an intensive program. The study also examined two student variables—time spent using and attitude toward the CALL lessons—as well as four cognitive/affective characteristics—field independence, ambiguity tolerance, motivational intensity, and English‐class anxiety. English proficiency was measured by the TOE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 45 publications
1
45
2
Order By: Relevance
“…Abraham (1985) reported that FI learners of ESL learned an advanced grammatical rule best in CALL materials that provided a deductive presentation, whereas the FD learners did better in CALL materials that presented examples. Chapelle and Jamieson (1986) showed that the FD learners had more positive attitudes toward the CALL component of their ESL program than the FI learners, even when motivation was controlled for. Finally, in examining the correlates of learning strategy use, Jamieson and Chapelle (1987) found that strategy use should be assessed in conjunction with cognitive style.…”
Section: Fid and Callmentioning
confidence: 99%
See 1 more Smart Citation
“…Abraham (1985) reported that FI learners of ESL learned an advanced grammatical rule best in CALL materials that provided a deductive presentation, whereas the FD learners did better in CALL materials that presented examples. Chapelle and Jamieson (1986) showed that the FD learners had more positive attitudes toward the CALL component of their ESL program than the FI learners, even when motivation was controlled for. Finally, in examining the correlates of learning strategy use, Jamieson and Chapelle (1987) found that strategy use should be assessed in conjunction with cognitive style.…”
Section: Fid and Callmentioning
confidence: 99%
“…The rules versus examples formats for grammar teaching, for example, might realistically be offered to learners studying grammar online. CALL materials such as those used in Chapelle and Jamieson's (1986) study could be offered to the FD learners, and a parallel set developed for the FI learners less fond of that kind of instructional design. Jamieson and Chapelle's (1987) study suggests that it may be useful to consider the amount of learner control and help options for different task types and learners in a CALL program.…”
Section: Fid and Callmentioning
confidence: 99%
“…Chapelle and Jamieson (1986) studied the use of CALL lessons in the acquisition of English as a second language and reported that students who worked harder at learning English spent a lot of time using CALL and had a more positive attitude toward it. They also reported a significant relationship between language learners' motivation and computer use and attitude.…”
Section: Call Attitudementioning
confidence: 99%
“…Applying CALL in the classroom could increase students' motivation because it is one of notable techniques nowadays (Chapelle & Jamieson, 1986;Chang & Lehman 2002;King, 2002;Torii-Williams, 2004;Ushioda, 2011).…”
Section: Computer Assisted Language Learning (Call) and Motivationmentioning
confidence: 99%